2015
DOI: 10.1007/s00425-015-2337-x
|View full text |Cite
|
Sign up to set email alerts
|

The fungal endophyte Epichloë typhina improves photosynthesis efficiency of its host orchard grass (Dactylis glomerata)

Abstract: Main conclusionAccording to the results presented in this paper the fungal endophyteEpichloë typhinasignificantly improves the growth, PSII photochemistry and C assimilation efficiency of its hostDactylis glomerata.In this paper, we present a comprehensive study of the impact of the endophytic fungi Epichloë typhina on its plant hosts’ photosynthesis apparatus. Chlorophyll a fluorescence, gas exchange, immuno-blotting and spectrophotometric measurements were employed to assess photosynthetic performance, chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
58
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 63 publications
13
58
0
2
Order By: Relevance
“…During the host's vegetative phase, the fungal pathogen causes no distinctive symptoms, reminiscent of plant endophytes – organisms that colonize plant tissue without causing apparent disease. In endophytes it has been shown that – despite the lack of explicit infection symptoms – the presence of a second organism within the host and their mutual interaction can lead to distinct changes in the physiology, morphology and growth of the host plant (Latchs & Christensen, ; Varma et al ., ; Olejniczak & Lembicz, ; Dupont et al ., ; Larriba et al ., ; Rozpadek et al ., ). Stunted growth of head smut‐infected plants has been previously reported (Gallart et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…During the host's vegetative phase, the fungal pathogen causes no distinctive symptoms, reminiscent of plant endophytes – organisms that colonize plant tissue without causing apparent disease. In endophytes it has been shown that – despite the lack of explicit infection symptoms – the presence of a second organism within the host and their mutual interaction can lead to distinct changes in the physiology, morphology and growth of the host plant (Latchs & Christensen, ; Varma et al ., ; Olejniczak & Lembicz, ; Dupont et al ., ; Larriba et al ., ; Rozpadek et al ., ). Stunted growth of head smut‐infected plants has been previously reported (Gallart et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Hibberd and Quick (2002) reported that CO 2 produced in roots can be transported to the shoot; stem cells in tobacco are supplied with C for photosynthesis from the vascular system and not from stomata. In this way, Rozpadek et al (2015) suggest that upon endophyte colonization, host plant undergoes changes in its photosynthetic apparatus, leading to increased light harvesting and photosynthesis efficiency.…”
Section: Transpiration (E) and D) Water Use Efficiency (Wue) Of Habamentioning
confidence: 99%
“…Interestingly, the expression of PsaC, as well as its protein abundance, was downregulated in E+. In numerous studies, the improved growth of symbiotic plants was accompanied by the upregulated synthesis of chlorophyll (Rozpądek et al, ; Vafadar, Amooaghaie, & Otroshy, ; Zuccarini, ). The measured concentration of chlorophyll did not differ in the E+ and E− A. thaliana and A. arenosa , indicating that improved photosynthesis resulted from more effective utilization of the absorbed solar energy rather than the ability to use a larger amount of incident light for photochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports show that the photosynthetic efficiency (PSII efficiency and carbon assimilation) is improved in plants inoculated with various microorganisms, suggesting that the plant adjusts to the additional sink for carbohydrates (Newman et al, 2003;Rozpądek et al, 2015Rozpądek et al, , 2016. The fungal-dependent upregulation of photosynthetic efficiency has usually been attributed to the improved acquisition of essential nutrients, such as N and P. However, it cannot be ruled out that upregulated carbon assimilation in symbiotic plants occurs via other mechanisms (Kaschuk, Kuyper, Leffelaar, Hungria, & Giller, 2009).…”
mentioning
confidence: 99%